2022
DOI: 10.3390/pharmaceutics14102065
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons of Macrophage Immunomodulation in the Healing of Diabetic Foot Ulcers

Abstract: Diabetic foot ulcers (DFUs) are one of the most costly and troublesome complications of diabetes mellitus. The wound chronicity of DFUs remains the main challenge in the current and future treatment of this condition. Persistent inflammation results in chronic wounds characterized by dysregulation of immune cells, such as M1 macrophages, and impairs the polarization of M2 macrophages and the subsequent healing process of DFUs. The interactive regulation of M1 and M2 macrophages during DFU healing is critical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…Wound healing is a very orderly and highly controlled process that requires the integration of complex cellular and molecular events characterized by distinct but overlapping phases: homeostasis, inflammation, cell proliferation, cell migration, angiogenesis and re-epithelialization [ 64 ]. During the initial phase, the role of macrophages is essential both to eliminate non-functional host cells and bacteria and create a favorable environment for tissue regeneration and repair [ 65 ]. Two distinct types of macrophages can be recognized: M1 macrophages, which function as pro-inflammatory mediators, and M2 macrophages, which act as natural feedback regulators from M1 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Wound healing is a very orderly and highly controlled process that requires the integration of complex cellular and molecular events characterized by distinct but overlapping phases: homeostasis, inflammation, cell proliferation, cell migration, angiogenesis and re-epithelialization [ 64 ]. During the initial phase, the role of macrophages is essential both to eliminate non-functional host cells and bacteria and create a favorable environment for tissue regeneration and repair [ 65 ]. Two distinct types of macrophages can be recognized: M1 macrophages, which function as pro-inflammatory mediators, and M2 macrophages, which act as natural feedback regulators from M1 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Sustained polarization of M1-type macrophages leads to a prolonged inflammatory response and persistent oxidative stress. 65 Another major reason for the failure of diabetic wounds to heal is redox imbalance due to excessive oxidative stress and decreased antioxidant capacity. 66 The combination of azilsartan and NF-kB inhibitor (Bay11-7082) has been reported to promote apoptosis in hepatocellular carcinoma cells by increasing reactive oxygen species (ROS) production and upregulating oxidation levels.…”
Section: Discussionmentioning
confidence: 99%
“…Tese researchers showed that maintaining HbA1c levels between 7.0% and 8.0% promotes the healing of diabetic ulcers, and patients with better blood sugar on admission heal rapidly. Previous studies have confrmed that hyperglycemia is not conducive to ulcer healing at any stage, as it weakens the phagocytosis and chemotaxis of neutrophils, hinders the synthesis of collagen, impedes the migration of keratinocytes, and induces endothelial progenitor cell dysfunction and polarization of M2 macrophages [20][21][22][23]. However, only a few studies have used experimental data to illustrate the positive efect of intensive glycemic control on diabetic ulcers.…”
Section: Discussionmentioning
confidence: 99%